AKSARA: Early Childhood Parenting E-BOOK as a Smart Parenting effort for Millennial Parents - Wulandari, Helnia; Putra, Yudithia Dian; Anisa, Nur (Universitas Negeri Malang, 2024)
Parenting children in the digital age has a profound influence on their character development and creativity. Millennials tend to use technology and the internet skillfully, and they often rely on online resources, especially social media, for parenting guidance. While technology can provide educational benefits, the use of the internet also poses challenges such as the spread of misinformation. Therefore, it is important for millennial parents to seek accurate and trustworthy information in educating their children. Character education is also increasingly important in building critical thinking, creativity and problem-solving skills in children. Early childhood character education supported by smart parenting can help instill positive traits and habits in children. This research uses the Research and Development (R&D) method and the ADDIE model to create the AKSARA E-Book which aims to help millennial parents in Malang City in parenting for early childhood. This E-Book provides valid and effective parenting